Risk of residual/recurrent cervical diseases in HPV-positive women post-conization depends on HPV integration status - Wenyu Lin; Yuxuan Huang; Yan Zhang; Lixiang Huang; Hongning Cai; Guanxiang Huang; Ye Li; Qiaoyu Zhang; Huifeng Xue; Binhua Dong; Pengming Sun (Infectious Agents and Cancer)
Abstract Background It is crucial to identify post-operative patients with HPV infection who are at high risk for residual/recurrent disease. This study aimed to evaluate the association between HPV integration and clinical outcomes in HPV-positive women after cervical conization, as well as to identify HPV integration breakpoints. Methods This retrospective study analyzed data of 791 women who underwent cervical conization for cervical intraepithelial neoplasia grades 2–3 (CIN2-3) between September 2019 and September 2023, sourced from the Fujian and Hubei cervical lesion screening cohorts. Among these, 73 women with HPV infection post-conization underwent HPV integration test within 3 months after a positive HPV test. HPV integration test was performed using the high-throughput viral integration detection (HIVID), a sensitive method for genome-wide survey of HPV integration breakpoints. Results Among the 73 participants with HPV infection post-conization, 10 cases (13.7%) were positive for HPV integration. The logistic regression analysis showed a higher residual/recurrent lesions risk in patients with HPV integration (OR = 3.917, p = 0.048). According to the Kaplan-Meier analysis, age ≥ 45 years (p = 0.016) and HPV integration (p = 0.035) were associated with a higher risk of residual/recurrent CIN at the 1-year follow-up. HPV 52 accounted for the majority of HPV integration genotype (3/10, 30.0%). Surprisingly, HPV 16 had the highest number of HPV average integration sequencing reads (n = 129), followed by HPV 31, 58, 52, 59, 35, and 39. The study also identified 13 HPV breakpoints, including TP63, TLR4, USP10, etc. Conclusions HPV integration was identified as an independent risk factor for residual/recurrent CIN in HPV-positive women post-conization. Women with positive HPV integration should pay attention to careful post-treatment follow-up.